CAN RURAL AREAS BENEFIT FROM ONLINE REVIEWS? MANAGING TOURIST SENTIMENTS IN RURAL ACCOMMODATION IN OHRID (NORTH MACEDONIA) - Andreeski, Cvetko; Matlievska, Margarita; Petrevska, Biljana (Economics of Agriculture, 2025)
This paper investigates factors influencing tourist satisfaction with rural accommodation, crucial for the sustainable development of rural areas. Recognizing that accommodations are important for rural economies, this study performs a sentiment analysis. It analyzes 4,557 online reviews from tourists visiting the rural areas of the east coast of Lake Ohrid (North Macedonia). Results reveal 15 factors grouped into four clusters: ‘Facility’, ‘Surrounding’, ‘Service’, and ‘Site’. The ‘Surrounding’ cluster has the most profound impacts on tourist satisfaction, consistently generating strong positive sentiments due to the excellent natural landscape in which rural accommodations are located. The ‘Facility’ cluster generally impacts negative sentiments, while ‘Service’ displays mixed sentiments. The ‘Site’ cluster reveals partially positive and mixed but negative sentiments. Such variability suggests a need for further managerial analysis and targeted improvements. This research provides practical suggestions for managers of rural accommodation to understand tourist emotions, optimize service quality, and foster sustainable rural tourism development.